The choice of modeling firm heterogeneity and trade restrictions - Matthew T. Cole (University College Dublin, UCD School of Economics, 2009)
There has been great focus in the recent trade theory literature on the introduction of firm heterogeneity into trade models. However, these models tend to rely heavily on symmetry assumptions and assume melting iceberg transport costs as the only form of trade restrictions. Moreover, a standard assumption is that firms differ across marginal cost, yet empirical evidence suggests this is not the only important source of heterogeneity. I provide a highly tractable model, in which firms differ across fixed costs, that qualitatively maintains the main results of these models, but allows for asymmetric changes in trade restrictions, a necessary step towards studying strategic trade policy. In addition, I highlight the differences in the effects on product variety associated with changes in an ad valorem tariff, iceberg transport costs, and additional beachhead costs to become an exporter. This is important as there are potential offsetting effects on firm entry.
hdl:10197/2618
Keywords: F10; F13; F15; 330; Intra-industry trade; Trade policy; Firm heterogeneity; Monopolistic competition